6.1k views
0 votes
Use substitution to solve each system of equations.
y = –6x– 19
6 x – 5 y = –13

User Arthis
by
4.7k points

1 Answer

2 votes

Answer:

Like you said, we will use substitution to solve the system to get rid of y.


y = -6x - 19\\6x - 5y = -13\\\\6x - 5(-6x - 19) = -13\\\\6x + 30x + 95 = -13\\\\36x + 95 = -13\\\\36x = -108\\\\x = -3

Next, we will use what we found for x and plug it into one of the original equations to solve for y. I will use the first equation.


y = -6(-3) - 19\\\\y = 18 - 19\\\\y = -1

Finally, we can now create the solution for this system.


(-3, -1)

User James Parker
by
5.1k points